Significance of uncertainty in explaining institutional change in Douglass C. North’s approach - Przesławska, Gabriela (Ekonomia i Prawo. Economics and Law, 2019)
Motivation: Studies on nature and effects of uncertainty in a non-ergodic world became in Douglass Cecil North’s concept a starting point for explanation of economic changes mechanism. The origin of North’s studies on uncertainty is related to one of key research problems relevant to the emergence of New Institutional Economics (NIE) approach, that is answering the question why some countries are rich and others poor. This problem, according to NIE representatives, cannot be satisfactorily explained in the framework of neoclassical paradigm based on assumptions of perfect information, ideal rationality of market actors and zero transaction costs. Aim: The purpose of the article is to present D.C. North’s concept of uncertainty as a source of beliefs and creating institutions (‘rules of the game’) which place human environment in order. Results: North’s breakthrough legacy is in emphasizing the role of human intentionality, growth in the stock of knowledge, as a result of human learning, and common cultural heritage in determining the direction and dynamics of economic changes. Considerations included in the article will enable proving the significance given by North to institutions in reducing uncertainty resulting from the nature of non-ergodic world and thus creating basic incentives for growth and evolutionary economic changes. Finally, the analysis conducted for that purpose in this article will show the original contribution of D.C. North’s institutional-cognitive approach to the development of NIE (and economic theory in general) in explaining institutional conditions of development.